Ethnobotanical Study of Potential Food-Utilization of Shade and Undercover Vegetation in the Coffee Agroforestry Landscape, Kalibaru District, Banyuwangi Regency - Pribadi, Titanio Auditya; Nurrofik, Agus; Bilbina Evabian, Camelia Hanum; Yuwafi, Hamdan (Directorate of Research and Community Services, 2024)
Agroforestry is a cultivation system that integrates crops like coffee with various vegetation, as applied in the Kalibaru District. The local community utilizes an agroforestry system by combining shade and undercover plants that can be utilized as food. The objective of this study was to collect a diversity of edible vegetation and investigate the local utilization. Data was collected by vegetation analysis and ethnobotanical studies related to their use. The result showed that 22 species of shade plants and 22 species of undercover plants were edible. The highest use value of shade species in coffee agroforestry are Leucaena leucocephala, Musa paradisiaca, Syzygium aromaticum, Carica papaya, and Artocarpus heterophyllus. Meanwhile, the highest use values in undercover species are Capsicum frutescens, Manihot esculenta, Colocasia esculenta, and Maranta arundinacea. The highest index of cultural significance for shade species is shown in Carica papaya, Leucaena leucocephala, Parkia speciosa, and Musa paradisiaca. Meanwhile, the highest index of cultural significance for undercover species is C. frutescens, L. esculentum, P. amarylifolius, and C. longa. This area can support local food resources and serve as a means of cultural preservation.